EFEKTIVITAS BUKU AJAR ISU SOSIAL KONTEMPORER BERBASIS NILAI ISLAM TERHADAP PENGUATAN KARAKTER RELIGIUS DAN KEJUJURAN MAHASISWA IPS - Henni Endayani (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2026)
This study aims to determine the effectiveness of a contemporary social issues textbook based on Islamic values in improving the religious and honesty character of Social Studies (IPS) students. The research employed a development research method. The development model used was the 4D model, consisting of four stages: Define, Design, Development, and Dissemination. The product trial was conducted among students of the Social Studies Education Program (Tadris IPS), specifically class IPS-1 in the seventh semester. The results showed that the Contemporary Social Issues Textbook Based on Islamic Values was effective in improving students’ religious and honesty character. The classical minimum mastery achievement reached 99%, indicating that the textbook can effectively enhance the religious and honesty character of IPS students. Therefore, it can be concluded that the contemporary social issues textbook based on Islamic values is feasible and effective as a learning resource for character development among Social Studies students.